Sexual Function after Staged Penile Urethroplasty with Oral Mucosal Graft: A Single-Center Prospective Analysis - Amir Taimur Khan, Hazratullah, Hamza Khan Shahbazi, Syed Muhammad Haider, Moath Ahmad Abdullah Almuradi, Muhammad Aness Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current study aims to assess erectile, ejaculatory and anatomical changes following staged penile urethroplasty with oral mucosal graft including outcomes re-evaluation after a set period of time in men with complex urethral strictures. Methods: This study was a prospective cohort study of 33 men who underwent staged penile urethroplasty with oral mucosal graft in Khyber Teaching Hospital Peshawar from July 2023-August 2024. Patients completed their sexual function assessment prior to and after the surgery using the Sexual Health Inventory for men (SHIM) and the Male Sexual Health Questionnaire Ejaculatory Short Form (MSHQ-EjD). Penile curvature, length, and sensitivity were assessed subjectively using a non-validated questionnaire. Changes in scores were analyzed using linear regression and descriptive statistics were used to summarize patient-reported outcomes. Results: The cohort had mean age 45years (SD: 11.2) and BMI 27.6kg/m^2(SD: 4.1). Stricture causes included failed hypospadias repair (52%), lichen sclerosus (27%) and previous urethroplasty (52%). Median follow up after the second stage was 6.3 months (IQR: 3.5–13.3). No clinical significance change was found in SHIM (Δ = −0.64, 95% CI: –3.00–1.72) or MSHQ-EjD score (Δ = 1.55, 95% CI: – 1.53–4.63). Subjectively 23% reported new penile curvature, 55% reported decreased length and 45% reported altered sensitivity. Satisfaction with intercourse increased in 32% (SHAM Q5) while 40% reported decreased bother by ejaculation (MSHQ-EjD Q4). Only 1 patient was on post-operative erectile dysfunction medication. Conclusion: As assessed with validated instruments, staged penile urethroplasty with oral mucosal grafting OMG has minimal effects on erectile and ejaculatory functions. On the other hand, subjective anatomical changes (sensitivity, curvatures, length) are commonplace and necessitate proper counseling prior to surgery. These insights are relevant to the expectations of patients and offer suggestions for further research on objective measurements of anatomy of the penis. Keywords: urethroplasty, sexual dysfunction, penile curvature, oral mucosal graft, erectile function, ejaculatory function.